CREATIVE ATTITUDES OF 6-GRADE PRIMARY SCHOOL PUPILS - Kiełbasa, Marzena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Teachers’ recognition of the pupils’ creative potential is far from easy because of the complexity, ambiguity and multifaceted quality of the phenomenon of creativity. The activity of diagnosing pupils’ creative attitude calls for identifying the structure of their creative behaviour. Analysis of the data obtained in the study helped determine the level of the creative attitude of the pupils taking part in the study on the scale of heuristic and non-conformist behaviours.